Radiation tests of real-sized prototype RPCs for the Phase-2 Upgrade of the CMS Muon System. (10th August 2016) - Lee, K.S.; Cho, S.W.; Choi, S.Y.; Hong, B.; Go, Y.; Kang, M.H.; Lim, J.H.; Park, S.K.; Cimmino, A.; Crucy, S.; Fagot, A.; Gul, M.; et al.
Abstract: We report on a systematic study of double-gap and four-gap phenolic resistive plate chambers (RPCs) for the Phase-2 upgrade of the CMS muon system at high η . In the present study, we constructed real-sized double-gap and four-gap RPCs with gap thicknesses of 1.6 and 0.8 mm, respectively, with 2-mm-thick phenolic high-pressure-laminated (HPL) plates. We examined the prototype RPCs with cosmic rays and with 100-GeV muons provided by the SPS H4 beam line at CERN. To examine the rate capability of the prototype RPCs both at Korea University and at the CERN GIF++ facility, the chambers were irradiated with 137 Cs sources providing maximum gamma rates of about 1.5 kHz cm −2 . For the 1.6-mm-thick double-gap RPCs, we found the relatively high threshold on the produced detector charge was conducive to effectively suppressing the rapid increase of strip cluster sizes of muon hits with high voltage, especially when measuring the narrow-pitch strips. The gamma-induced currents drawn in the four-gap RPC were about one-fourth of those drawn in the double-gap RPC. The rate capabilities of both RPC types, proven through the present testing using gamma-ray sources, far exceeded the maximum rate expected in the new high- η endcap RPCs planned for future phase-II runs of the Large Hadron Collider (LHC).